Ecocritical Discourse Analysis Of Construction Of Environmental Issues In English Language Textbooks Of Khyber Pakhtunkhwa - Shumaila Ashee, Sania Siraj, Dr. Anbarin Fatima (Migration Letters, 2024)
The study investigates the discourses on environmental problems presented in middle school English textbooks, in Khyber Pakhtunkhwa. Ecocritical discourse analysis (ECDA) is used to scrutinize environmental content and demystify the ingrained ideologies presented in these textbooks. The English textbooks of grades 6 to 8, for the academic year 2024- 2025 are selected as they are the most recent published textbooks, and are in use in the current academic year. The study’s findings demonstrate that pollution, deforestation, and biodiversity have been introduced to the students as significant environmental problems. However, the nature and causes of these issues are presented uncritically —the issues are stated without identifying the actors and contributors to these problems. It is also ascertained that the selected textbooks serve the interests of the government, and many national or multinational companies, while overlooking the needs of the students and general public who are the ultimate affectees of the prevalent climate conditions. Thus, teachers using these textbooks must introduce the real situation on the ground by evaluating the role of the human beings in creating such a crisis. Furthermore, it is also strongly recommended that to raise awareness, more contextualized content should be provided to the students to raise awareness and introduce critical perspectives, to foster environmental stewardship.